JENIS-JENIS LAMUN DI PERAIRAN LAGUNA TASILAHA DAN PENGEMBANGANNYA SEBAGAI MEDIA PEMBELAJARAN BIOLOGI - Yusniati, Yusniati (JSTT, 2015)
This research was aimed at identifying and describing kinds of sea grass on Laguna Tasilaha Waterworks, and producing Biology instructional media in the form of a guided book used in conducting instruction.This research was carried out on Laguna Tasilaha Waterworks, Banawa Selatan Sub-district, Donggala Regency, Central Sulawesi Province. Using survey method with tehniques crossing. Futhermore, the result of this research will be developed to learning instrument. Seagrass taken by using plot that placed purposively. The research result has identified that there were six kinds of the sea grass based on two family groups. The first group was Hydrocharitaceae consisting of Enhalus acoroides, Thalassia hemprichii, and Halophia ovalis. The second group, on the other hand, was Potamegetonaceae comprising Cymodocea rotundata, C. serrulata, and Halodule uninervis. The development result produced the pocketbook. It was validated by 88.40% content, design, and media expert, 81.03% educator assessment, 83.26% small group assessment,Â  and 91.74% large group assessment. Therefore, the average percentage was 86%. If it was converted into the eligibility criteri, it was eligible and can be used as Biology instructional media.